THE CONCEPT OF DEPRECIATION AS AN ACCOUNTING CATEGORY. - Bombright, James C. (The Accounting Review, 1930)
Abstract Conventionally, depreciation is a deduction from the original cost, the actual cost of the assets. That actual cost of the assets is not written up generally in order to accord with the present value of the property. There have been accountants who have recognized the objection to the accepted definition that depreciation represents loss of value, and have attempted to find substitutes. A more plausible theoretical definition of depreciation is "Amortized Costs." That is to say, it is that portion of the cost of the asset which has, in fact, been written off, which has been charged against the operating expenses of the previous year. It would seem to imply that a business which, wisely or unwisely, has not in fact written off anything for depreciation, has not suffered a depredation, because if a business does not amortize its capital cost, then there is no amortized capital cost, and by definition there would not be any depreciation. There should be the use of accrued depreciation accounting, rather than the use of retirement reserves in public utility regulation.